Inflation targeting in the Czech Republic - Audrlický, Dan (2023)
The aim of the thesis Inflation targeting in the Czech Republic was to understand better the monetary policies, inflation targeting policy, their role in economy and factors influencing inflation outside of the control of the Czech National Bank influence when using its monetary policy tools. An empirical observation of inflation data between the years 1998 to 2021 has provided insights about the performance of the CNB in meeting its inflation targets while using the inflation targeting regime. The years in which the inflation deviated outside of the CNB's target were analyzed throughout the period 1998-2021 and the inflation influencing factors were listed such as external and internal factors and others.